Allelopathic plants. 7. Sunflower (Helianthus annuus L.) - Azania, AAPM; Azania, CAM; Alves, PLCA; Palaniraj, R.; Kadian, H. S.; Sati, S. C.; Rawat, L. S.; Dahiya, D. S.; Narwal, S. S. (Int Allelopathy Foundation, 2003)
Sunflower is an annual dicotyledonous plant, herbaceous, erect and native of North America. It is thermo- and photo-insensitive, hence, can be grown round the year in sub-tropical and tropical countries. Only two spp. H. annuus and H. tuberosum are cultivated for food, remaining spp. are ornamentals, weeds and wild plants. However, H. annuus is allelopathic and inhibit the growth and development of other plants thus reducing their productivity. Much information is available about the allelopathic effects of sunflower crop on following crops in crop rotations. Although it is harmful to all crops, but, is less harmful to crops of Graminae family than other families. It seems that the harmful effects of sunflower in crop rotations are due to release and accumulation of root exudates during crop growth in soil. Soil incorporation of its fresh (green manure) or dry biomass in soil is inhibitory to both crops and weed spp. Several allelochemicals have been characterized from the H. annuus, which inhibit the seed germination and seedling growth of A. albus, A. viridis, Agropyron repens (Elymus repens), Ambrosia artemsiifolia, Avena fatua, Celosia crustata, Chenopodium album, Chloris barbara, Cynodon dactylon, D. sanguinalis, Dactyloctenium ageyptium, Digitaria ciliaris, Echinochloa crus-galli, Flaveria australasica, Parthenium hysterophorus, Portulaca oleracea, Sida spinosa, Trianthema portulacastrum, Veronica perisca the inhibitory effects of this crop may be used for weed management with less herbicides for sustainable agriculture.
Keywords: Allelochemicals; A. albus; A. viridis; Agropyron repens (Elymus repens); Ambrosia artemsiifolia; Avena fatua; Celosia crustata; Chenopodium album; Chloris barbara; clusterbean; cotton; cowpea; cucumber; Cynodon dactylon; D. sanguinalis; Dactyloctihium ageyptium; Digitaria ciliaris; Echinochloa crus-galli; Flaveria hysterophorus; pearlmillet; Pennisetum glaucum; Phaseolus aureus; pigeonpea; Portulaca oleracea; radish; rice; sesame; Sida spinosa; sorghum; soybean; sunflower; tomato; Trianthema portulacastrum; Veronica perisca